1998
DOI: 10.1080/00039899809605698
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Oxidized Nitrogen: Lipid Peroxidation and Neonatal Health Risk

Abstract: Pregnant women exposed to extensive environmental contamination by oxidized nitrogen compounds were studied at parturition, their neonatal health status was assessed and the involvement of oxidative stress in pathology was evaluated. Methemoglobin in maternal and cord blood was measured as a biomarker of individual exposure. Blood lipid peroxides and glutathione (reduced and total) were determined as oxidative stress biomarkers. Birthweight, Apgar scores, and clinical diagnosis at birth were used as neonatal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 18 publications
0
26
1
1
Order By: Relevance
“…Increased lipidic peroxidation in the maternal or foetal compartment has been associated to prematurity. It has been observed in experimental studies that NO 2 during pregnancy induces lipid peroxidation in the placenta, high post-implantation embryonic lethality, and disturbances of postnatal development [36]. (7) The pathogenesis of IUGR is produced by an abnormal reaction between the trophoblast and the uterine tissues within the first weeks of gestation, therefore, an alteration of growth may result from a suboptimal placentation and maternal hemodynamic maladaptation [37] which could be due to exposure to air pollutants during the first month of gestation [3].…”
Section: Resultsmentioning
confidence: 99%
“…Increased lipidic peroxidation in the maternal or foetal compartment has been associated to prematurity. It has been observed in experimental studies that NO 2 during pregnancy induces lipid peroxidation in the placenta, high post-implantation embryonic lethality, and disturbances of postnatal development [36]. (7) The pathogenesis of IUGR is produced by an abnormal reaction between the trophoblast and the uterine tissues within the first weeks of gestation, therefore, an alteration of growth may result from a suboptimal placentation and maternal hemodynamic maladaptation [37] which could be due to exposure to air pollutants during the first month of gestation [3].…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to NO 2 during pregnancy is associated with an increased lipid peroxidation in the placenta, elevated postimplantation embryonic lethality, and disturbances of postnatal development (Tabacova et al, 1998). It has also been demonstrated that maternal exposure to NO 2 can increase the risk of pregnancy complications as a consequence of initiation of the formation of cell-damaging lipid peroxides and a decrease in maternal antioxidant reserves (Tabacova et al, 1998). Moison et al (1993) found that an increased lipid peroxidation of surfactants in maternal or fetal tissue compartments has been associated with preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…Tabacova et al [56] have documented the involvement of oxidative stress in the pathogenesis of adverse prenatal effects associated with exposure to oxidized nitrogen compounds. Pregnant women exposed to extensive environmental contamination by oxidized nitrogen compounds were studied at parturition and their neonatal health status was assessed.…”
Section: Exposure To Oxidized Nitrogen Species (Toxic Substances) Andmentioning
confidence: 99%